2019
DOI: 10.21037/atm.2019.11.63
|View full text |Cite
|
Sign up to set email alerts
|

A new management strategy for renal angiomyolipomas: superselective arterial embolization in combination with radiofrequency ablation

Abstract: Background: The present study analyzed the safety and efficacy of superselective arterial embolization (SAE) combined with radiofrequency ablation (RFA) to treat renal angiomyolipoma (RAML).Methods: This retrospective study included the clinical data of 6 patients with RAML treated between March 2016 and October 2017. All patients underwent RFA treatment immediately after SAE guided by angio-computed tomography (angio-CT). The tumor size, renal function and complications, and time to recurrence were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The volume shrinkage in the cohort was significant and within the reported range of 27% to 55.1% ( 11 , 20 , 26 ). In the clinical model, tumor shrinkage rate was significantly related to angiomyogenic tissue ratio, which was consistent with previous studies ( 27 , 28 ). Hocquelet et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The volume shrinkage in the cohort was significant and within the reported range of 27% to 55.1% ( 11 , 20 , 26 ). In the clinical model, tumor shrinkage rate was significantly related to angiomyogenic tissue ratio, which was consistent with previous studies ( 27 , 28 ). Hocquelet et al.…”
Section: Discussionsupporting
confidence: 91%
“…1% (11, 20, 26). In the clinical model, tumor shrinkage rate was significantly related to angiomyogenic tissue ratio, which was consistent with previous studies (27,28). Hocquelet et al (9) reported a significant difference in tumor volume reduction between RAMLs with less than 50% fat and those with more than 50% fat (84% vs. 50%; p < 0.00001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, interventional therapy, including selective arterial embolization (SAE), ablation and SAE combined with ablation, has become an important treatment option, especially for patients with acute rupture with hemorrhage and those intolerant to surgery. Currently, it is believed that interventional therapy should be considered when the maximum diameter of renal AML is >4 cm or relevant clinical symptoms appear 44 . However, postoperative renal impairment, tumor recurrence, and retreatment after embolization remain urgent problems to be solved in clinical practice.…”
Section: Treatment Of Renal Epithelioid Angiomyolipomamentioning
confidence: 99%
“…Currently, it is believed that interventional therapy should be considered when the maximum diameter of renal AML is >4 cm or relevant clinical symptoms appear. 44 However, postoperative renal impairment, tumor recurrence, and retreatment after embolization remain urgent problems to be solved in clinical practice. In this challenging context, standard chemotherapy regimens for soft tissue sarcomas have only been shown to be effective in a small subset of patients, and long-term results remain unsatisfactory.…”
Section: Treatment Of Renal Epithelioid Angiomyolipomamentioning
confidence: 99%